Importance of Abnormal Chloride Homeostasis in Stable Chronic Heart Failure. (January 2016) - Grodin, Justin L.; Verbrugge, Frederik H.; Ellis, Stephen G.; Mullens, Wilfried; Testani, Jeffrey M.; Tang, W.H. Wilson
Abstract : Background—: The aim of this analysis was to determine the long-term prognostic value of lower serum chloride in patients with stable chronic heart failure. Electrolyte abnormalities are prevalent in patients with chronic heart failure. Little is known regarding the prognostic implications of lower serum chloride. Methods and Results—: Serum chloride was measured in 1673 consecutively consented stable patients with a history of heart failure undergoing elective diagnostic coronary angiography. All patients were followed for 5-year all-cause mortality, and survival models were adjusted for variables that confounded the chloride–risk relationship. The average chloride level was 102±4 mEq/L. Over 6772 person-years of follow-up, there were 547 deaths. Lower chloride (per standard deviation decrease) was associated with a higher adjusted risk of mortality (hazard ratio 1.29, 95% confidence interval 1.12–1.49; P <0.001). Chloride levels net-reclassified risk in 10.4% ( P =0.03) when added to a multivariable model (with a resultant C-statistic of 0.70), in which sodium levels were not prognostic ( P =0.30). In comparison to those with above first quartile chloride (≥101 mEq/L) and sodium (≥138 meq/L), subjects with first quartile chloride had a higher adjusted mortality risk, whether they had first quartile sodium (hazard ratio 1.35, 95% confidence interval 1.08–1.69; P =0.008) or higher (hazard ratio 1.43, 95% confidence interval 1.12–1.85; P =0.005). However, subjects with first quartile sodium but above first quartile chloride had no association with mortality ( P =0.67). Conclusions—: Lower serum chloride levels are independently and incrementally associated with increased mortality risk in patients with chronic heart failure. A better understanding of the biological role of serum chloride is warranted. Abstract : Supplemental Digital Content is available in the text.